Path reduction factor for microwave terrestrial links derived from the Malaysian meteorological radar data - Khamis, Nor Hisham (2005)
Attenuation due to rain is a major concern in transmission of microwave signals. The effect of rain attenuation is more pronounce when signals are being transmitted at higher frequencies. For tropical countries like Malaysia, rain occurs almost yearound and in most instances, much heavier than temperate region. Even rain itself, does not distribute evenly in a region experiencing precipitation. This gives rise to the need of a correction or reduction factor when calculating attenuation due to rain. This topic has been the focus of many researches. However, many of these researches were done in temperate regions, making it necessary for a study using local data. This study utilized the local weather radar data obtained from the Meteorological Department of Malaysia, and data from two rain gauge networks installed in UTM, Skudai campus. From the analysis of the radar data, a reduction factor is deduced. The reduction factor obtained in this study follows the same pattern as other models but has a lower value as the path link increases. This shows that attenuation due to rain is lower than as predicted using other models. Rain rate distribution and rain cell size distribution is also formulated from radar data. R0.01 of 120.907 mm/hr agrees very well with the ITU-R and the Meteorological Department of Malaysia values. Using data from the rain gauge networks, the profile and the size of rain cells at different rain rates are determined. This study finds that most rain cells in Malaysia are highly convective with an average cell size of 1.2 to 1.5 km. All the information are important for attenuation predictions, link budget estimation, microwave system planning, slant path rain attenuation modeling and remote sensing of the earth’s surface, and have important applications in attenuation mitigation techniques such as space diversity. Further study can be done with more precise, elaborate, and sophisticated measuring systems such as Doppler or polarimetric radar,complemented with microwave links and rain gauge networks.